Algebra (Factoring)

What's the easiest way to factor this completely?

2x^4-10x^2-72

A step-by-step solution would really help me a lot. Thanks :)

  1. 👍 0
  2. 👎 0
  3. 👁 155
  1. 2(x^4-5x^2-36)
    2(x^2+4)(x^2-9)
    2(x^2+4)(x-3)(x+3)

    1. 👍 0
    2. 👎 0
    posted by Steve

Respond to this Question

First Name

Your Response

Similar Questions

  1. math,factoring,help

    Can someone please show me step by step how to do these. I've read the book and there examples and It is just not clicking. Directions: Factor each of the following polynomials completely Problem:#1 14x^2-20x+6 Directions:Find all

    asked by Jasmine20 on January 31, 2007
  2. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

    asked by Valerie on October 22, 2019
  3. Math

    William multiplied (-2x+1-3y)(-0.5x) and got the wrong solution. Review his work and identify the step in which William made his first error. Step 1 (-2x+1-3y)(-0.5x) Step 2 (-0.5x)(-2x-3y+1) Step 3 -0.5x(-2x)-0.5x(-3y)-0.5x(1)

    asked by Cherie on June 10, 2019
  4. math

    10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

    asked by help on November 13, 2017
  5. math

    Omar wanted to know if x−5 is a factor of the polynomial p(x)=x3−6x2−x+30. He applied the Factor Theorem and concluded that x−5 is a factor of p(x), as shown in the following work. Step 1: p(5)=53−6(52)−5+30 Step 2:

    asked by Noise on November 28, 2019
  1. algebra 2

    f(x) =x^4 - x^3 -4x^2 +4. find factor and graph. I only factor to this step: (x^3 - 4x-4)(x-1) = f(x) but i don't know how to continue this step to require factor more completely and graph it. Please help. this is algebra 2. Thank

    asked by Anonymous on December 10, 2015
  2. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

    asked by Anonymous on October 25, 2018
  3. math 10 grade

    4y2 + 25y + 6 can you explain how to do step by step thanks Factor completely

    asked by Amanda on December 7, 2009
  4. Algebra

    How do I solve for the elimination method: 5x + 3y= -7 and 7x - 2y =13 (step 1); 10x + 6y =-14 and 21x -6y = 39 ( step 2), 31x/31= 25/31, x= 25/31 (step 4). But after that I get lost. Can somebody help me out please.

    asked by A.W. on March 6, 2009
  5. algebra

    how do I factor a polynomial completely, please tell me step by step.

    asked by Kreidan on March 23, 2011

More Similar Questions